Fundamental drivers of prosperity in the European Union and Western Balkans countries - Jovanović Gavrilović, Biljana; Gligorić, Mirjana (Industrija, 2018)
In this paper the aim is to identify key drivers that have contributed the most to the prosperity of European Union and Western Balkan countries in the 2007-2016 period. Empirical analysis is based on data for cumulative growth rate of values of nine original Legatum Prosperity Index (LPI) pillars and on implementation of Multivariate Data Analysis. Using Principal Component Analysis, four principal components are obtained and we named them: Economic Environment, Social Infrastructure, Institutional Framework and Life Conditions. Based on standardised score values of four new variables, we distinguish the countries that had the highest positive and negative score in each component. With cluster analysis based on LPI pillars growth rates, four clusters of countries have been formed: the first cluster consists of three Western Balkan countries, the second and third of, respectively, ten and four mostly new EU member state countries, and fourth of fourteen predominantly “old” EU member countries. The analysis points out the fundamental drivers of prosperity in countries belonging to different clusters according to changes in values of nine LPI pillars in the previous decade. In all observed countries it is possible to identify certain similarities in the change of components of prosperity, as they are EU members or candidates for membership.
Keywords: Drivers of Prosperity; Cluster Analysis; Principal Component Analysis; Legatum Prosperity Index; Component; Analysis